Evaluation Of The Method Of Stress Characteristics For Estimation Of The Soil Bearing Capacity - Mohammed Y. Fattah; Mohammed F. Aswad; Mohammed M. Mahmood (Engineering and Technology Journal, 2008)
The classical bearing capacity theories rely on the superposition of three separatebearing capacities – a technique that is inherently conservative – but they also rely ontabulated or curve-fitted values of the bearing capacity factor, Nγ, which may beunconservative. Further approximations are introduced if the footing is circular(multiplicative shape factors are used to modify the plane strain values of , Nc, Nq and Nγ) orif the soil is non-homogeneous (calculations must then be based on some representativestrength). By contrast, the method of stress characteristics constructs a numerical solutionfrom first principles, without resorting to superposition, shape factors or any other form ofapproximation.In this paper, the validation of the method of stress characteristics is tested by solvinga wide range of bearing capacity problems. The results are compared with classical bearingcapacity theories; namely, Terzaghi, Myerhof, Hansen and Vesic methods.It was concluded that the bearing capacity predicted by the method of stresscharacteristics for the case of a circular footing in clay ranges between (3.7 – 4.0) greater thanTerzaghi, Meyerhof, and Vesic methods. This means that the method is not conservative forthis case and can be dependent for economic design of foundations. The bearing capacitypredicted by this method increases linearly with (D/B).For all values of the angle of friction, φ, the method reveals bearing capacity values forsmooth footings greater than Terzaghi and Hansen and smaller than Meyerhof and Vesictheories. Considering the foundation to be rough, the method gives bearing capacity valuesgreater than all other methods. The difference increases as the angle of internal friction(φ) increases. This makes the method unreliable for rough foundations.